The Influence of Organizational Culture and Locus of Control on Organizational Citizenship Behavior and Its Impact on Employee Performance at PT PLN (Persero) Central Java & DIY Yogyakarta Distribution Main Unit - Nabilah Fatin Daulay; Audita Nuvriasari (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to examine the influence of organizational culture, locus of control, organizational citizenship behavior, and employee performance. The research design employed quantitative method using explanatory research approach. The sample comprised the entire population, totaling 170 participants. Data was collected through questionnaire surveys. Data analysis was conducted using SmartPLS 4.0, involving three stages: outer model, inner model, and hypothesis testing. The conclusion drawn from this study is that organizational culture, locus of control, and organizational citizenship behavior have a positive and significant impact on employee performance.